2020
DOI: 10.3390/ijerph17061881
|View full text |Cite
|
Sign up to set email alerts
|

Association between Leucocyte Telomere Length and Risk of Hearing Loss in the General Population: A Case-Control Study in Zhejiang Province, China

Abstract: Limited studies have assessed the relation between telomere length and risk of hearing loss; moreover, they have reported equivocal associations. In the first case-control study, the subjects were chosen from the general population of Zhejiang province in order to assess the association between leucocyte telomere length and risk of hearing loss from 2016 to 2018. A total of 817 cases (55.93 ± 8.99 years) and 817 age-, sex- and residential city-matched controls (55.91 ± 9.03 years) were included for analysis. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…A large number of studies have been conducted to prove the correlation between MTL and age-related chronic diseases or disorders, such as cardiovascular disease, cognitive performance, and cancer mortality (Huang et al, 2020;Linghui et al, 2020;Shen et al, 2020;Hoffmann et al, 2021). However, studies on the relationship between MTL and hearing loss, which is a very common age-related chronic disorder, are quite limited, with results of inverse or negative associations between them Wang et al, 2019;Zhang et al, 2020). Our results are rather consistent with the results of two previous casecontrol studies of the Chinese population (Liu X. et al, 2017;Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A large number of studies have been conducted to prove the correlation between MTL and age-related chronic diseases or disorders, such as cardiovascular disease, cognitive performance, and cancer mortality (Huang et al, 2020;Linghui et al, 2020;Shen et al, 2020;Hoffmann et al, 2021). However, studies on the relationship between MTL and hearing loss, which is a very common age-related chronic disorder, are quite limited, with results of inverse or negative associations between them Wang et al, 2019;Zhang et al, 2020). Our results are rather consistent with the results of two previous casecontrol studies of the Chinese population (Liu X. et al, 2017;Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that longer telomere length was negatively related to hearing loss in older adults . In another study, telomere length was considered a predictive biomarker of hearing loss at an early stage (Zhang et al, 2020). However, telomere length was not correlated with hearing levels in children and midlife adults in a third study (Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a case-control study, it was observed that patients with shorter LTL (only middle-age and older individuals were included) had an increased presence of ischemic (OR: 1.37; 95% confidence interval [CI]: 1.06-1.77) and hemorrhagic stroke (OR: 1.48; 95% CI: 1.08-2.02) compared with the highest telomere length tercile [45]. At the same time, patients with low LTL had a much higher risk of plaque occurrence (risk ratio: 1.49; 95% CI: 1.09-2.03), as well as a higher risk of their plaque progression (risk ratio: 1.61; 95% CI: 1.26-2.07).…”
Section: Cellular Senescencementioning
confidence: 99%
“…Since chronic exposure to excessive noise levels is among the leading risk factors for hearing loss mediated by noise-induced inflammation, oxidative stress, and endothelial damage, further evidence of a contribution of noise in biological aging might arise from studies examining the association between biomarkers of aging and hearing loss. A recent case-control study from China examined the association between telomere length and risk of hearing loss, including 817 cases and 817 matched control subjects [ 164 ]. Decreased odds of hearing loss was observed for subjects in the highest quartile of telomere length, compared to the lowest quartile (OR 0.53, 95% CI 0.38 to 0.74).…”
Section: Human Evidence On the Association Between (Traffic) Noisementioning
confidence: 99%